Exploring Listening Strategies, Activities, And Resources of English Education Department Lecturers - Lestari, Tri Indah; Nor, Hidayah (FKIP - Universitas Tanjungpura, 2024)
Listening is essential for understanding spoken language, and lecturers must use various strategies, activities, and resources appropriate to students' skills to ensure effective learning. The purpose of this study is to explore the listening strategies, exercises, and resources EFL lecturers use when teaching listening courses. Using narrative inquiry for the methodology, the data for this study were gathered through interviews with two lecturers teaching listening courses. The collected data were subjected to a narrative analysis. The results of this study show that lecturers follow several important guidelines, such as incorporating listening into more general language skills, applying intrinsic motivation strategies, and encouraging the growth of listening strategies. Lecturers